2022
DOI: 10.1186/s12951-022-01315-x
|View full text |Cite
|
Sign up to set email alerts
|

Nanoarchitectured prototypes of mesoporous silica nanoparticles for innovative biomedical applications

Abstract: Despite exceptional morphological and physicochemical attributes, mesoporous silica nanoparticles (MSNs) are often employed as carriers or vectors. Moreover, these conventional MSNs often suffer from various limitations in biomedicine, such as reduced drug encapsulation efficacy, deprived compatibility, and poor degradability, resulting in poor therapeutic outcomes. To address these limitations, several modifications have been corroborated to fabricating hierarchically-engineered MSNs in terms of tuning the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 534 publications
(696 reference statements)
0
47
0
Order By: Relevance
“…The presence of impurities, (e.g., metals) on nanoparticle surface may play an important role in nanosilica toxicity [ 135 ]. In addition, the modified surface of mesoporous silica nanoparticles by some surfactants or chemical agents can also modulate cytotoxic responses [ 140 ]. Interestingly, particle surface area could also be transformed by natural molecules, such as ascorbic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of impurities, (e.g., metals) on nanoparticle surface may play an important role in nanosilica toxicity [ 135 ]. In addition, the modified surface of mesoporous silica nanoparticles by some surfactants or chemical agents can also modulate cytotoxic responses [ 140 ]. Interestingly, particle surface area could also be transformed by natural molecules, such as ascorbic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous Met can induce macrophages to polarise toward the anti-inflammatory phenotype M2, resulting in the secretion of a series of anti-inflammatory cytokines, such as vascular endothelial growth factor (VEGF) and transforming growth factor-β, to promote tissue repair [ 18 , 19 ]. The silica-based materials have been deemed safe by the United States Food and Drug Administration for medicinal applications [ 20 ]. Mesoporous silicon nanoparticles (MSNs) are porous microspheres with internal mesoporous structures that facilitate the storage and controlled release of drugs [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cytotoxic drugs have been demonstrated that some drugs induce immunogenicity by expressing tumor-specific antigens and MHC-I molecules on the surface of cancer cells [31]. Collectively, rational design of bioinspired nanomaterials with cell membrane camouflaging technology for metal complex is a new strategy to overcome their shortcomings and enhance the cancer treatment [32][33][34].…”
Section: Introductionmentioning
confidence: 99%